Identification and characterization of low resistivity low contrast zones in a clastic outcrop from Sarawak, Malaysia - Iqbal, M.A. (2019)
Zones with low resistivity low contrast (LRLC) are usually overlooked due to the absence of high-end well logging techniques in the older oil/gas fields. The Nyalau Formation outcrop (stratigraphically equivalent to offshore cycles I and II) from Sarawak, offers a good opportunity to identify and characterize LRLC zones through integrated approaches. Seven facies of the Nyalau Formation had been identified, which are: 1) low angle cross-bedded sandstone (CBSS), 2) laminated sandstone (LSS), 3) heterolithic sandstone (HSS), 4) bioturbated sandstone (BSS), 5) clay-rich sandstone (CSS), 6) mudstone (MS), as well as 7) trough CBSS (TCBSS). Apparent resistivity was determined for brine (60 kpm) saturated core plugs at a temperature of 75 Â°F by employing the sample core induced polarization technique. The measurement of resistivity was calibrated based on offshore salinity, as well as surface and subsurface temperature of the Sarawak. The geological and petrophysical characteristics were analyzed through field observations and lab analyses. The findings of the study revealed that the cutoff value of resistivity found at LRLC zones in Nyalau Formation was 12.6 Î©-m. Accordingly; LSS, BSS, and CSS facies appeared to derive from LRLC zones. The main causes that generate such LRLC zones are laminations, thin bedding, bioturbation, and clay minerals. The dominant effect portrayed by mixed layers of illite/smectite and smectite in LRLC zones could be attributed to their high cation exchange capacity (CEC). Two varying resistivity trends were discovered based on the variances detected in clay types for different facies. A negative correlation was found between resistivity and porosity within high resistivity zones, while a positive relationship within the LRLC zones. Disparity in the resistivity-porosity correlation is deduced to be associated with clay mineralogy. This study suggests that LRLC zones are expected to be present in shallow marine clastic reservoirs of offshore cycles (I and II), where the offshore reflects Nyalau Formation. Â© 2018 Elsevier B.V.